Studies of electricaland optical properties of sn doped and undoped ZnO thin films by the spray pyrolysis method - Arato Tovar, Ana María; García Montes, Saida Mayela; Castillo, G. Alan; Das Roy, Tushar Kanty (2010)
Undoped and tin (So) doped zinc oxide (ZnO) !hin film have been deposited by spray pyrolysis me1hod of zinc acetate and tin ch1oride. The concentrationratio of[Sn]/ [Zn] was varied from 0-5 at %. The effect of doping Sn on physical and optica1 properties was studied by diffcrent techniques such as X-ray di:ffraction for structura 1 characterization, SEM forthickness and morpbology, UV-Vis spectroscopy for optical properties, Hall effect and photoconductivity for electrical characterization. X-ray di:ffraction (XRD) patterns show Iba. Iba fllms deposited are polycrystalline with (002) plane as Iba preferential orientatioo. According 10 Scherrer's equation, grain size values on the fi1ms are found between 30 - 45 nm with spberica1 shape. Optical transmittance was about 92% in visible range for the optimum film ami shows that the band gap decreases from 3.29 to 3 .17 e V.